SOME CHALLENGES TO THE ENFORCEMENT OF THE COMPETITION LAW IN INDONESIA - Maarif, Syamsul (Gadjah Mada International Journal of Business, 2004)
Indonesian competition law known as Law No. 5 of 1999 was adopted on the fifth of March 1999 and took effective a year later, the fifth of March 2000. Since the adoption of the Law we are witnessing business players have changed in the ways they run their businesses. We are also witnessing challenges that need to be dealt with if we want Law No5 effective to reach its objectives. This article discloses some of those challenges. The most difficult one to deal with is the resistance by the court to the existence of the Indonesian Antimonopoly Authority (KPPU).